If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9w+12w=-15
We move all terms to the left:
-9w+12w-(-15)=0
We add all the numbers together, and all the variables
3w+15=0
We move all terms containing w to the left, all other terms to the right
3w=-15
w=-15/3
w=-5
| (x-1)^2=16 | | 5(-2x+5)+x-5=-43 | | X²+9x-1620=0 | | t-9-3.2=2 | | 43=y+18 | | 2m2+5m+16=8 | | 2z-z-1=11 | | .25x-5=20 | | 4x/3+7/3=0 | | 4c+6c=10 | | (2x-1)^2=81 | | 1/2(c+3)=2/5c-3/4 | | t+9-9.2=9 | | -20=-4x–6x | | 14=1/3y | | 16x+9=16x-48 | | k+4—5(k+2)=3k—2. | | y²-6=2²+3²-6-(-3) | | -(-13+b)=27 | | 5x+7-3x=1/2(4x+12)+1 | | -44=-14x+28+6x | | 5x+4+3x+10=180 | | F(0)=2x^2+x-1 | | |8-3x|=0 | | 2x+8=5×-3 | | 7w-13=5w-7 | | -6x-18=-72 | | 3/2-w=5/2 | | -7(x+1)=-41x+55 | | -4m+1=-19 | | 5x-16·3x-12=0 | | –3x+0.8=–1.4 |